Small RNA Illumina library preparation for plant virus identification and sequencing - International Potato Center (2024)
Small interfering RNA (siRNA) sequencing and assembling technology (sRSA) has become an efficient and powerful tool for the identification of known viral pathogens, occurring at extremely low titers, as well as the discovery of novel viruses, without the necessity of any prior knowledge. This video shows step by step how to prepare siRNA libraries for high-throughput sequencing and assembling of siRNA for virus identification.